Pengembangan Interactive Multimedia Power Point Presentation (IMPPT) untuk Pengajaran Phonetics - Ike Dian Puspita Sari; Indrawati Pusparini (Jurnal Inspirasi Pendidikan, 2020)
In phonology, students will be familiar with phonetics which is specifically emphasize phonetics’ articulation and the sound. This study used Research and Development method. Researchers developed Interactive Multimedia Power Point Presentation (IMPPT) which can be used to teach phonetics. There are some stages done to develop IMPPT. Those stages are need analysis, data collection, product design and validation, and product testing. Product testing was also carried out as a consideration for the next steps. If the result was not satisfied, the researcher revised the design to obtain the final product. There were three aspects concerned as criteria of IMPPT, namely visual aspect, audio aspect, and material aspect. Those three aspects were validated based on assessment rubrics made by researcher. The range in the rubric is 1-5. The visual aspect showed the highest percentage, in which it was 35%. The second highest percentage was audio aspect. In material aspect, the total score was 23 (32%).